Rancang Bangun Monitoring Tumpukan Sampah Pada Saluran Air Berbasis Long Range - Lanang, Jabbar Kala; Taqwa, Ahmad; fadhli, Mohammad (Department of Electrical Engineering, University of Patria Artha, 2022)
A water channel is a building made for the process of draining water. The water channel will drain water from a high place to a lower place. Waterways are commonly used to drain rainwater, irrigate rice fields and household wastewater. The problem that often arises in waterways is the accumulation of garbage. Garbage that accumulates can clog drains. Clogged drains can cause environmental problems such as flooding, water pollution, sources of unpleasant odors, and breeding grounds for mosquitoes. Garbage problems that arise in waterways must be addressed immediately. One form of solving the problem of piles of garbage in waterways is the process of monitoring the state of the waterways. The process of monitoring waterways aims as a form of monitoring the condition of waterways. In the current technological era, the process of monitoring water flow can be done remotely by utilizing internet of things technology. The monitoring process using internet of things technology can facilitate monitoring work because there is no need to visit the location to see the condition of the waterways. The design of monitoring waste piles in loRa-based waterways is a tool design to facilitate the process of monitoring waste in waterways. The monitoring process is carried out by paying attention to the water discharge to determine the condition of the water channel. The process of sending data on waterways uses the LoRa transmission system.